Force-Modulated Equilibria of Mechanophore-Metal Coordinate Bonds - Epstein, Eric; Kim, Tae Ann; Kollarigowda, Ravichandran H.; Sottos, Nancy R.; Braun, Paul, V (American Chemical Society, 2020)
We describe reversible force-induced metal-ligand coordination in spiropyran (SP) mechanophore linked PDMS elastomers. In the presence of lithium, calcium, or magnesium ions, SP is in equilibrium with its metal coordinating merocyanine (MC) isomer. Tensile force drives the equilibrium to higher concentrations of MC-metal complexes. Removal of the mechanical bias shifts the equilibrium back to the initial distribution of SP and metal coordinated MC. We demonstrate that this process is fully reversible and repeatable. Optical absorbance measurements reveal differences in coordination strengths of different metal cations. Stronger coordination causes greater spontaneous MC activation and consequently smaller changes in absorbance after mechanical activation. With Li(I), the weakest coordinating ion, a 2.7 MPa tensile load generates up to 1.9x more MC-metal complexes, whereas only an similar to 1.2x enhancement is observed with Mg(II), the strongest coordinating ion. We show that spontaneous activation of MC-metal complexes is suppressed by modifying the solvation character of the PDMS matrix. The effect of metal ion coordination strength on the susceptibility of spirocyclic bonds to mechanically triggered rupture is investigated by using density functional theory. This study lays the foundation for expanding the utility of SP mechanophores toward applications including force-generated chemical potential gradients and reversible, force-activated metal-ligand polymer cross-linking.